Resilience and Growth in the Small States of the Pacific - Khor, Hoe (International Monetary Fund, 2016)
Pacific island countries face unique challenges to realizing their growth potential and raising living standards. This book discusses ongoing challenges facing Pacific island countries and policy options to address them. Regional cooperation and solutions tailored to their unique challenges, as well as further integration with the Asia and Pacific region will each play a role. With concerted efforts, Pacific island countries can boost potential growth, increase resilience, and improve the welfare of their citizens.